An Underwater Quadrotor Control with Wave-disturbance Compensation by a UKF. Issue 2 (2020) - Ohhira, T.; Kawamura, A.; Shimada, A.; Murakami, T.
Abstract: This paper proposes an unscented Kalman filter (UKF) with disturbance estimation for an underwater quadrotor control system by utilizing backstepping control. Autonomous underwater vehicles (AUVs) have been attracted attention to scientific and commercial applications. The tasks in those applications are such as surveys and inspections for various objects underwater in narrow space. In this study, a quadrotor type robot, in which high-performance results are obtained for aerial application, is regarded as AUVs. The quadrotor robot is a smaller system than general AUVs and has suitable merits for work in a narrow place. On the other hand, since the quadrotor system is small and light in weight, it is more susceptible to underwater waves than conventional AUVs. Therefore, consideration of a technique to suppress or to reject the influences of the waves in the control systems is a must. This paper proposes a UKF system including a second-order model of input disturbance for estimating the influence of waves and an accurate quadrotor state simultaneously. Additionally, the disturbance estimation performance assists in make robustness as its estimated disturbance is rejected to actual disturbance. Finally, the usefulness of the proposed system is shown via simulations of position control for the underwater quadrotor affected by a wave effect model.